IKKα in the regulation of inflammation and adaptive immunity. (20th March 2007) - Lawrence, T.; Bebien, M.
Abstract : Inflammation is a beneficial response to insult or injury which plays an important role in orchestrating the adaptive immune response. The resolution of acute inflammation is an active process that involves the release of anti-inflammatory mediators and the termination of pro-inflammatory signalling pathways coincident with leucocyte apoptosis and phagocytic clearance and the migration of antigen-presenting cells from the site of inflammation to the local lymphatic tissue. The latter process is required for the development of adaptive immunity and immunological memory. The NF-κB (nuclear factor κB) pathway is an important regulator of inflammation and immunity; NF-κB activation is controlled by IKK [IκB (inhibitor of NF-κB) kinase] complex, which regulates NF-κB activation in response to pro-inflammatory stimuli. The IKK complex has two catalytic subunits, IKKα and IKKβ; recent research shows that these highly homologous kinases have distinct roles in inflammation and adaptive immunity. Here, we discuss the emerging roles for IKKα in the tight regulation of inflammation and the development of adaptive immune responses.